An Integrated Bioprocess for the Expansion and Chondrogenic Priming of Human Periosteum‐Derived Progenitor Cells in Suspension Bioreactors. Issue 2 (20th November 2017) - Gupta, Priyanka; Geris, Liesbet; Luyten, Frank P.; Papantoniou, Ioannis
Abstract : The increasing use of microcarrier‐based suspension bioreactors for scalable expansion of adult progenitor cells in recent years reveals the necessity of such approaches to address bio manufacturing challenges of advanced therapeutic medicinal products. However, the differentiation of progenitor cells within suspension bioreactors for the production of tissue modules is of equal importance but not well investigated. This study reports on the development of a bioreactor‐based integrated process for expansion and chondrogenic priming of human periosteum‐derived stem cells (hPDCs) using Cultispher S microcarriers. Spinner flask‐based expansion and priming of hPDCs were carried out over 12 days for expansion and 14 days for priming. Characterization of the cells were carried out every 3rd day. Our study showed that hPDCs were able to expand till confluency with fold increase of 3.2±0.64 and to be subsequently primed toward a chondrogenic state within spinner flasks. During expansion, the cells maintained their phenotypic markers, trilineage differentiation capabilities and viability. Upon switching to TGF‐β containing media the cells were able to differentiate toward chondrogenic lineage by clustering into mm‐sized macrotissues containing hundreds of microcarriers. Chondrogenic priming was further evidenced by the expression of relevant markers at the mRNA level while maintaining their viability. Ectopic implantation of macrotissues highlighted that they were able to sustain their chondrogenic properties for 8 weeks in vivo. The method indicated here, suggests that expansion and relevant priming of progenitor cells can be carried out in an integrated bioprocess using spinner flasks and as such could be potentially extrapolated to other stem and progenitor cell populations. Abstract : The rapid growth in the field of Tissue Engineering and Regenerative Medicine highlights the need for bioreactor‐based scalable expansion and differentiation of adult progenitor cells. In order to address this limitation, our study aims to develop a microcarrier‐based integrated bioprocess for expansion and chondrogenic differentiation of human periosteum‐derived progenitor stem cells. On receiving proper cue, the expanded cells were able to aggregate to mm sized macrotissues which maintained chondrogenic properties both in vitro and in vivo.